Thyroidectomy in patients with amiodarone-induced thyrotoxicosis - U. A. Tsoy; A. A. Shekhovtsova; E. V. Ivanikha; M. A. Salov; I. N. Danilov; T. V. Andrejchenko; A. B. Dalmatova; L. V. Belousova; E. N. Grineva (Вестник хирургии имени И.И. Грекова, 2021)
The OBJECTIVE of the study was to analyze the experience of performing thyroidectomy (TE) in patients with amiodarone-induced thyrotoxicosis (AmIT) at our centre.METHODS AND MATERIALS. The study included 12 patients with AmIT who underwent TE. Medical records were analyzed to assess the features of the AmIT and indications for TE. We also studied the operation protocols and postoperative follow-up data. Intraoperative, early and long-term postoperative complications were recorded. The long-term TE results were evaluated by the dynamics of the left ventricular ejection fraction (LVEF) based on the echocardiography data.RESULTS. The main indications for TE included the resistance of thyrotoxicosis to medication and worsening of the cardiac pathology. No cases of thyrotoxicosis progression or thyrotoxic crisis were registered during the operation. The vocal cord paresis developed in one case, completely restored in a year. Blood loss was minimal in all cases. Other intraoperative complications were absent. Not a single death was registered in the early postoperative period. At this period, a short paroxysm of atrial fibrillation resolved on its own was registered in patient with arrhythmogenic right ventricular dysplasia. A patient with biventricular chronic heart failure of a high functional class died 39 days after the operation due to a massive pulmonary thromboembolism. The long-term results of TE were evaluated in eight patients. In four out of five patients with initially reduced LVEF, it increased. In three patients with initially normal LVEF, it did not change.CONCLUSION. Thyroidectomy is an effective and safe treatment in patients with AmIT, including those with the persistent thyrotoxicosis and severe cardiac pathology. The success is possible when the preparation of patients for the intervention is carried out by a team of specialists experienced in treating of such patients.